Pharmaceutical compounding and dispensing - Langley, Christopher A.; Belcher, Dawn (London, United Kingdom : Pharmaceutical Press, 2012)
"This FASTtrack book has been designed to assist the student compounder in understanding the key dosage forms encountered within extemporaneous dispensing."-Publisher
Introduction -- Solutions -- Suspensions -- Emulsions -- Creams -- Ointments, pastes and gels -- Suppositories and pessaries -- Powders and capsules
Includes bibliographical references and index.
Keywords: DOSAGE FORMS